STRUCTURAL EQUATION MODEL AS A TOOL TO ASSESS THE RELATIONSHIP BETWEEN GRAIN YIELD PER PLANT AND YIELD COMPONENTS IN DOUBLED HAPLOID SPRING BARLEY LINES (HORDEUM VULGARE L.) - Mańkowski, Dariusz R.; Kozdój, Janusz; Janaszek-Mańkowska, Monika (Plant Breeding and Seed Science, 2016)
The aim of this study was to describe and characterize the relationships between yielding factors and grain yield per doubled haploid (DH) plant of spring barley as well as relation between yield components and duration of each stage of plant development. To describe these relations structure equation modeling was used. The study included plants of doubled haploid spring barley lines (Hordeum vulgare L.) derived from tworowed form of Scarlett cultivar. The SAS® system was used to analyze the model of relationships between grain yield per plant and yield components. Our results indicate that the number of spikes per plant and grain yield per spike had a direct and decisive influence on the grain yield of the investigated DH plants of spring barley. Based on the path model analysis it was found that the most important factor determining grain yield per DH plants of spring barley was the number of spikes per plant and the duration of tillering and shooting stages.